Revisiting the Phillips Curve and the Lucas Critique - Hossain, Md. Sharif (Journal of Economics and Behavioral Studies, 2013)
Many OECD countries are facing problems of high government debt and high unemployment. Consequently, a monetary stimulus is being increasingly viewed as a solution to curb the rising debt burden and stimulate economic growth. Some OECD countries are setting inflation target at 2% or even higher. In this paper we investigate the likely impact of inflation on unemployment for a panel of 10 highincome OECD countries, namely, Australia, Denmark, Iceland, Japan, Korea, New Zealand, Norway, Sweden, Switzerland and the United States. The period of study is 1970-2012. Results indicate a significantly positive long-run impact of inflation on unemployment. Granger causality indicates long-run bi-directional causality between inflation and unemployment. For the 10 OECD countries and the period of this study, the empirical findings support the Lucas critique: inflation and unemployment are positively correlated. A monetary stimulus, therefore, will most likely aggravate the unemployment scenario in the 10 OCED countries under study.